1983
DOI: 10.1029/jb088ib01p00546
|View full text |Cite
|
Sign up to set email alerts
|

Strain dependent attenuation: Observations and a proposed mechanism

Abstract: The measured attenuation (Q-•) of a rock is a function of a number of parameters, one of those being the applied strain amplitude. It is important to understand the effect that strain amplitude has on Q-• for several reasons: different measurement techniques use differing strain amplitudes and may measure a dissimilar Q-l, near source (large strain) wave propagation may behave highly non-linearly, and the strain amplitude dependence can provide insight into the attenuatiøn mechanism. A physical model based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…The estimate inevitably lacks precision because it relies on observations of both the pressure dependence of Young's modulus and the dependence of the quality factor on pressure and strain amplitude. Further, measurements of quality factor show that Q -1 is proportional to strain amplitude only at amplitudes greater than 10 -5 (see [22] for reference to their measurements). We ) / ( dp dQ dp…”
Section: Dynamic Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…The estimate inevitably lacks precision because it relies on observations of both the pressure dependence of Young's modulus and the dependence of the quality factor on pressure and strain amplitude. Further, measurements of quality factor show that Q -1 is proportional to strain amplitude only at amplitudes greater than 10 -5 (see [22] for reference to their measurements). We ) / ( dp dQ dp…”
Section: Dynamic Behaviormentioning
confidence: 99%
“…Measurements of Q -1 by Stewart et al [22] provide another way to estimate the value of λα j . The estimate inevitably lacks precision because it relies on observations of both the pressure dependence of Young's modulus and the dependence of the quality factor on pressure and strain amplitude.…”
Section: Dynamic Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors reported local-earthquake coda attenuation (Q c ) varying over time scales from several weeks to a few years, such as Chouet (1976Chouet ( , 1979, Aki (1980), Stewart et al (1983), Rhea (1984), Novelo-Casanova et al (1985), , Jin and Aki (1986), Peng et al (1986), ), Fehler et al (1988, Londono (1996), Gusev (1997), Del Pezzo et al (2004, Moncayo et al (2004), Novelo-Casanova et al (2006). The results were invariably interpreted by using the single-and multiple-scattering coda models, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar fashion, Stewart et al,20 have proposed a physical attenuation model based on complex crack structure and friction which, like Mavko, provides a Q-proportional to peak strain and which is also proportional to the crack density and the -4/3 power of the confining pressure.…”
mentioning
confidence: 99%